Short-term Functional Outcome of Corticosteroid Injection for Treatment of Trigger Finger in a Tertiary Care Center: A Prospective Observational Study - Shrestha, Rajesh; Roy, Rabindra; Jha, Rajesh Kumar; Rijal, Shreejal; Kushwaha, Rajdev Prasad (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Trigger finger is a common cause of painful digital dysfunction resulting from impaired gliding of the flexor tendon beneath a thickened A1 pulley. Corticosteroid injection is widely used as a first-line intervention for Quinnell Grades II and III trigger finger, but short-term outcomes in Nepalese clinical settings remain limited. This study aimed to evaluate short-term pain reduction and clinical improvement following intralesional injection in these grades. Methods: This prospective observational study was conducted in the Orthopedics Department of a tertiary care center from April 3, 2023, to April 2, 2024. Ethical approval was obtained from the Institutional Review Committee (Ref. No. 245). A convenience sampling technique was used. Each participant presenting with Quinnell Grade II or III trigger finger received a single intralesional injection containing 40 mg of methylprednisolone acetate mixed with 1 ml of 2% lignocaine. Pain was assessed using the Visual Analogue Scale (0–100 mm) at baseline, 1 month, and 3 months. Clinical resolution of triggering and any injection-related complications was systematically recorded. Data were analyzed using Statistical Package for the Social Sciences version 20.0. Visual Analogue Scale scores were analyzed using the paired t-test, Results: The mean baseline Visual Analogue Scale score was 74.50±13.10 mm, which showed a significant reduction to 18.70±16.80 mm at 1 month and further to 13.50±10.50 mm at 3 months (p<0.001). Complete resolution of triggering was achieved in 39 (98%) of the cases. One (2%) patient experienced recurrence and subsequently underwent percutaneous release. A single (2%) case of superficial injection-site infection was recorded, with no major complications reported. Conclusions: Intralesional corticosteroid injection produced marked short-term pain reduction and near-complete symptom resolution in Grade II and III trigger finger, with minimal complications. These findings support its role as an effective and practical first-line treatment in outpatient settings.